2021
DOI: 10.1155/2021/5512325
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Lung Adenocarcinoma Based on Immune Checkpoint and Screening of Related Genes

Abstract: Aims. Lung adenocarcinoma (LUAD) cells could escape from the monitoring of immune cells and metastasize rapidly through immune escape. Therefore, we aimed to develop a method to predict the prognosis of LUAD patients based on immune checkpoints and their associated genes, thus providing guidance for LUAD treatment. Methods. Gene sequencing data were downloaded from the Cancer Genome Atlas (TCGA) and analyzed by R software and R Bioconductor software package. Based on immune checkpoint genes, kmdist clustering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Chiba et al found that CLEC7A could promote natural killer cells to secrete cytotoxic factors and thus fight lung cancer through cell-to-cell contact ( Chiba et al, 2014 ). In this study, CLEC7A had a positive effect on the prognosis of LUAD patients, which was consistent with the findings of previous studies ( Zou et al, 2020 ; Zhou et al, 2021b ; Lin et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Chiba et al found that CLEC7A could promote natural killer cells to secrete cytotoxic factors and thus fight lung cancer through cell-to-cell contact ( Chiba et al, 2014 ). In this study, CLEC7A had a positive effect on the prognosis of LUAD patients, which was consistent with the findings of previous studies ( Zou et al, 2020 ; Zhou et al, 2021b ; Lin et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…The most relevant characteristic gene modules of this population were found by WGCNA, and four biomarkers that could be used as vaccination responses were found in these modules. Although previous studies have described LUAD immune subtypes (Wu et al, 2021;Zhao et al, 2021;Zhou et al, 2021), in the present study, we associated immune subtypes and mRNA vaccination for the first time. Drug sensitivity analysis of different immune subtypes showed significant differences in drug sensitivity among different subtypes, not only providing a reference for treatment strategies for populations not suitable for vaccination but also revealing the importance of individualized treatment.…”
Section: Discussionmentioning
confidence: 98%
“…The study of Guo et al reported a 10 immune-related gene model that could facilitate the management of immunotherapy in LUAD [ 34 ]. In addition, Zhou et al also established a nine-gene signature based on immune checkpoints to aid prognostic analysis in LUAD [ 35 ]. The aforementioned studies were confined to several-gene model, while the antitumor immune response effect was influenced by complex components of TIME.…”
Section: Discussionmentioning
confidence: 99%